PROFESSOR PETR KAZIMIROVICH YABLONSKIY (to the 60th anniversary of the birth) - E. G. Sokolovich; G. G. Guseva (Вестник хирургии имени И.И. Грекова, 2020)
The article is dedicated to the 60th anniversary of the birth of the outstanding representative of the St. Petersburg medical school and thoracic surgery of the country, the talented scientist and teacher, doctor of medical sciences, professor Petr Kazimirovich Yablonskiy. P. K. Yablonskiy is the founder of many progressive endeavors in medicine: the study of the fundamental principles of respiratory transplantation implemented in the world’s first successful simultaneous allotransplantation of the trachea (1991) and the first successful bilateral lung transplantation in the Russian Federation; the creation of the Russian school of interventional pulmonology and the St. Petersburg school of breast endovascular surgery; the development and implementation for the first time in world practice of the concept of using robot-assisted operations in the treatment of patients with pulmonary tuberculosis. Significant scientific potential and high organizational capabilities allowed P. K. Yablonskiy to lead and actively develop the Center for Intensive Pulmonology and Thoracic Surgery on the basis of the multidisciplinary city hospital; the Department of Hospital Surgery, and then the Faculty of Medicine of St. Petersburg University; St. Petersburg Research Institute of Phthisiopulmonology. The great experience in clinical medicine and the organization of public health contributed to his appointment as the chief freelance specialist – the thoracic surgeon of the Ministry of Health of the country, and also allowed him to head the Association of Thoracic Surgeons and the National Association of TB specialists, created by him.